Toward a novel theoretical approach for determining the nature of electronic excitations in quasi-two-dimensional systems. (10th August 2015) - Politano, A; Chiarello, G; Cupolillo, A
Abstract: The discovery of quasi-two-dimensional (Q2D) crystals has started a new era of materials science. Novel materials, atomically thin and mechanically, thermally and chemically stable, with a large variety of electronic properties are available and they can be assembled in ultrathin flexible devices. Understanding collective electronic excitations (plasmons) in Q2D systems is mandatory for engineering applications in plasmonics. In view of recent developments in the emerging field of graphene-based plasmonics, the correspondence between the theoretically calculated quantities and the observables experimentally measured in Q2D crystals is still unsatisfactory. Motivated by recent Nazarov's findings (Nazarov 2015 New J. Phys. 17 073018 ), here we discuss some crucial issues of current theoretical approaches as well as the computational methods applied to two-dimensional materials with special emphasis to cover their peculiarities, range of application and pitfalls.